Analysis of Factors Affecting Purchasing Decision Consumer of Coconut Cooking Oil at Modern Market In Semarang - Valentina Sri Basa Tambunan; Agus Setiadi; Edy Prasetyo (Publikasi Indonesia, 2023)
This study were aims to determine the characteristics of consumers of coconut cooking oil and analyze the factors that influence the purchase decisions of coconut cooking oil in the Modern Market of Semarang City. The study was conducted in Transmart Setiabudi, Gelael Sultan Agung, Farmer’s Market and Hypermart Semarang City in October - November 2022. The research method was a survey method with questionnaire. Sampling method was using the Accidental Sampling method with a total sample of 100 respondents. Data were analyzed descriptively and logistic regression analysis using SPSS software. The results showed that the product, price, location, social, individual and psychological simultaneously had a significant effect on coconut cooking oil purchasing decisions in the Modern Market of Semarang City. Variable product, price, location, social, individual and psychological partially had a significant effect on coconut cooking oil purchasing decisions in Semarang Modern Market. For coconut cooking oil producers that supply to the modern market to be able to improve the promotion dan culture can increase the demand for coconut cooking oil market.